PENGARUH KOMUNIKASI TENTANG IJIN MENDIRIKAN BANGUNAN (IMB) OLEH KANTOR PELAYANAN PERIJINAN TERPADU (KPPT) TERHADAP PARTISIPASI MASYARAKAT DALAM PENGURUSAN PEMBUATAN IJIN MENDIRIKAN BANGUNAN (IMB) DI KOTA CIREBON - Didi Saputra; Heriyani Agustina; Mukarto Siswoyo (Jurnal Ilmiah Publika, 2013)
Research by the author is the influence of communication on building permit (IMB) by unifiedlicensing offices (KPPT) for community participation in the management of the manufactureof building permit (IMB) in the city of Cirebon. The problem is that the writer suggestedparticipation in the manufacture of building permit (IMB) in the city of Cirebon less thanoptimal, the problem is suspected in non optimal result from the implementation of thecommunication by the unified licensing offices (KPPT) Cirebon. The research questionajuakan writer is, is there any influence by the office of the communication servicesintegrated permitting (KPPT) for community participation in the management ofmanufacturing IMB The method I used is quantitative (survey) The hypothesis that theauthors propose is as follows. "There is a positive and significant correlation betweencommunication by KPPT Cirebon terhapat community participation in the management of themanufacture of building permit (IMB) in the city of Cirebon". From the hypothesis can beformulated statistical hypothesis as follows:Ho (Null Hypothesis): rs count <of rs table, then the formulation of the problem is:"There is no positive and significant impact on the communication between the effect ofbuilding permit (IMB) by unified licensing offices (KPPT) on public participation in themanagement of the manufacture of building permit (IMB) in the city of Cirebon. Ha(Alternative Hypothesis): count rs> rs of the table, then the formulation of the problem is:"There is a positive and significant correlation between the influence of communication onbuilding permit (IMB) by unified licensing offices (KPPT) for community participation in themanagement of the manufacture of building permit (IMB) in the city of Cirebon.". In thisstudy obtained results that the communication made by KPPT good enough sufficient, but notoptimal segaimana seen from the successful implementation of the communication reached62.0% with a total score of 3019, while the participation of the community has been prettygood but not optimal, as the percentage is 60.9 % with a total score of 3702 Implementationof the communication by the close KPPT have an influence on public participation in themanagement of the manufacture of building permit (IMB) in the city of Cirebon. calculate thevalue of rs rs tables 0.220 0.642 sedangakan. Since rs rs count is greater than the table, thenthere is a positive and significant correlation between communication by KPPT influencepeople's participation in the management of the manufacture of building permit (IMB) in thecity of Cirebon. Thus, the authors propose a hypothesis that can be tested and accepted